Can cryptocurrencies act as a hedge to stock market volatility? Evidence from geopolitical risk and economic pocily uncertainty - Chua, Kar Hoon; Ng, Jasmine Kar Ying; Lee, Kai Zhean; Saw, Miao Qi (2022)
Recently, cryptocurrencies are gaining attention from investors, policymakers and researchers around the world. This research examines the hedging capabilities of cryptocurrencies (Bitcoin, Ethereum, XRP, and Dogecoin) against Cboe Volatility Index (VIX), Global Economic Policy Uncertainty (GEPU) and Geopolitical Risk (GPR). Monthly data starting from October 2015 to March 2021 is used for this research. This research will apply Pooled Ordinary Least Square (OLS) model, Fixed Effect Model (FEM) and Random Effect Model (REM) to examine the direct impact of Cboe Volatility Index (VIX) and the indirect impact of uncertainties (GEPU and GPR) on cryptocurrencies’ return. The regression models also have been proven that they are free from unit root through Levin-Lin-Chu Test, Im-Pesaran-Shin W-Stat Test, ADF-Fisher Chi-square Test and PP-Fisher Chi-square Test. By conducting Breusch-Pagan LM Test and Hausman Test, Pooled OLS model is shown to be the most suitable regression model in interpreting the result. In brief, the outcomes show that Cboe Volatility Index (VIX) as well as the indirect impact of Global Economic Policy Uncertainty (GEPU) and Geopolitical Risk (GPR) have no relationship with the cryptocurrencies’ return. In other words, cryptocurrencies can act as a hedge to these risks. Investors, policymakers and future researchers can gain valuable information through the results of this research.